Relationship between dyslipidemia and albuminuria in prediabetic adults: The Korea National Health and Nutrition Examination Survey 2011–2012 - Nam, Ga Eun; Han, Kyungdo; Kim, Do Hoon; Park, Yong Gyu; Yoon, Yeo Joon; Kim, Young Eun; Lee, Sangsu; Lee, Sungho; Roh, Yong Kyun (Endocrine, 2015)
This study aimed to estimate the relationship between various lipid abnormalities and albuminuria in Korean prediabetic adults. Data obtained from the Korea National Health and Nutrition Examination Survey (KNHANES) 2011–2012 were analyzed. The study consisted of 4,811 subjects in the normal glucose group and 3,872 in the prediabetic group. Prediabetes was defined by the fasting plasma glucose or hemoglobin A1c level. Albuminuria was defined as a urine albumin to creatinine ratio (UACR) ≥30 mg/g. Various parameters of dyslipidemia were assessed. No differences were observed in the prevalence of lipid abnormalities in prediabetic men with different values of UACR. Prediabetic women with increased urinary albumin excretion showed a significantly higher prevalence of lipid abnormalities. The proportion of mixed dyslipidemia was significantly higher in prediabetic women with albuminuria. Higher levels of total cholesterol, triglyceride (TG), low-density lipoprotein cholesterol (LDL-C), non-high-density lipoprotein cholesterol (non-HDL-C), and TC to HDL-C ratio, TG to HDL-C ratio, and LDL-C to HDL-C ratio were significantly associated with increased risk of albuminuria in prediabetic women. Conclusions: Several lipid abnormalities were significantly associated with the increased risk of albuminuria in prediabetic women. Hence, screening for lipid abnormalities may be helpful for identification of risk for albuminuria in prediabetic subjects.